Indigenous TAFE graduates : patterns and implications - Schwab, R. G.; Australian National University. Centre for Aboriginal Economic Policy Research (Canberra : Australian National University, Centre for Aboriginal Economic Policy Research, 1997)
This paper focuses on comparisons between indigenous and non-indigenous TAFE graduates and reveals some important similarities and differences between the two graduate groups.
Includes bibligraphical references.
Keywords: Aboriginal Australians -- Education -- Social aspects; Aboriginal Australians -- Education (Higher) -- Social aspects; Minorities -- Vocational education -- Australia; Technical education -- Australia; Education - Adult education; Education - Skills and curriculum - Vocational guidance; Education - Achievement; Australia